P254 THE ROLE OF GENDER IN CONGESTION STATUS EVALUATION IN PATIENTS WITH ACUTE HEART FAILURE. (18th May 2022) - Potenza, A; Scicchitano, P; Basile, M; Piscopo, A; Landriscina, R; Sasanelli, P; Trotta, F; Sanasi, M; Paolillo, C; Ciccone, M; Caldarola, P; Massari, F
Abstract: Background: The evaluation of congestion play a central role in the management of patients with acute heart failure (AHF).The impact of gender on congestion in patients with HF is still a matter of debate. The objective of this analysis was to evaluate the impact of gender on congestion status at admission of patients hospitalized for AHF. Methods: We consecutively enrolled 487 patients with AHF (50% female). We assessed peripheral edema, jugular venous distention (>10 cm), B–type natriuretic peptide (BNP), hydration status (by means of bioimpedance analysis), and estimated plasma volume (by means of the Duarte's formula [D–ePVS] and Kaplan–Hakim formula [KH–ePVS]). Results: Home medications and body mass index were not different between women and men. Women were older (79 yrs vs 77 yrs, P = 0.005), showed better left ventricular ejection fraction (mean 50% vs 38%, P < 0.001), and increased plasma concentrations in blood urea nitrogen (40 mg/dL vs 25 mg/dL, P = 0.02) and serum creatinine (1.5 mg/dL vs 1.5 mg/dL, P = 0.8). At physical examination, the number of patients with peripheral edema and jugular venous distention was not significantly different between women and men (53% vs 45% and 60% vs 55%, respectively). BNP levels (median 1100 pg/mL vs 994 pg/mL) and hydration status (78% vs 79%) were similar in women and men, while ePVS was higher in women (D–ePVS 6.0 ± 1.6 dL/gr vs 5.1 ± 1.5 dL/gr, P < 0.001; KH–ePVS 7.9% ± 13% vs –7.3 ±12%, P < 0.001). Conclusions: The evaluation of congestion in AHF using physical examination and multiparametric approaches was similar between women and gender. Women rather showed higher plasma volume as compared to male individuals.